1997
DOI: 10.1038/bjc.1997.124
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CA 15-3 serum levels and disease extent in predicting overall survival of breast cancer patients with newly diagnosed metastatic disease

Abstract: In order to study the relationship between circulating levels of CA 15-3 and the disease extent in predicting survival, we prospectively followed 312 breast cancer (BC) patients, from October 1988 to March 1995, from the time of first relapse. CA 15-3 values were assessed before treatment onset. Disease extent was defined as the percentage of liver or lung involvement and the number of bone segments positive at scintigraphy. The covariates were primary tumour characteristics (T, N and hormone receptor status) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
41
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 22 publications
(25 reference statements)
11
41
0
2
Order By: Relevance
“…3 In the vast majority of human adenocarcinomas this protein is over-expressed and hypo-glycosylated 4 exposing an immunodominant repetitive amino acid sequence. The overproduction and secretion of MUC1 is correlated with the progression of breast, 5 ovarian 6,7 and colon 8 carcinoma. In breast cancer patients MUC1 serum levels are used to monitor therapy and for early detection of recurrences.…”
mentioning
confidence: 99%
“…3 In the vast majority of human adenocarcinomas this protein is over-expressed and hypo-glycosylated 4 exposing an immunodominant repetitive amino acid sequence. The overproduction and secretion of MUC1 is correlated with the progression of breast, 5 ovarian 6,7 and colon 8 carcinoma. In breast cancer patients MUC1 serum levels are used to monitor therapy and for early detection of recurrences.…”
mentioning
confidence: 99%
“…Clinical uses of this marker include monitoring of patients with breast cancer (Duffy, 1999;Duffy et al, 2006), prognosis (McLaughlin et al, 2000), recurrence (Busetto et al, 1995;Molina et al, 1996;Molina et al, 1999) and metastasis (Elston et al, 1999;Thompson et al, 1991). CA15-3 level correlate exclusively with tumor size; higher CA15-3 serum level was found in advanced cancer stages, higher grades and metastasis (Berruti et al, 1994;Gang et al, 1985;Kikuchi et al, 1987;Theriault et al, 1989Theriault et al, :2007Tampellini et al, 1997;Gion et al, 2002). CA15-3 level increased in 10% stage I breast cancer disease, 20% stage II disease, 40% stage III disease, and 75% with stage IV disease (Duffy 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also reported that disease free survival of the patients with CA15.3 levels of 40 U/ml was half of those exhibiting normal levels of CA15.3 . Another study by Tampellini et al demonstrated that median OS of the patients whose CA15.3 value was ≤30 kilounits at the time of metastasis was longer than those with higher CA15.3 level (Tampellini et al, 1997). On the other hand a study conducted by De La Lande et al revealed that the time between the diagnose of breast cancer and detection of high levels of CA15.3 is prognostically significant (De La Lande et al, 2002).…”
Section: Discussionmentioning
confidence: 97%